Comparison of the Provisions of ACI318-19 Code and Eurocode on the Structural Design and Cost Analysis, of a High-rise Concrete Building Subjected to Seismic & Wind Forces - Oussadou, Samy Elhadi (2021)
This work aims to compare two codes; ACI 318-19 and Eurocode in terms of lateral effect on high-rise building, focusing on the seismic and wind provisions, and since these two forces effect the structural elements geometry, thus the cost comparison was included, by comparing the amount of reinforcement used. Since both of the codes have different standards and factors, therefor it is expected that there will be some differences in the structural design. This research contain design and analyses of a high-rise building consisting of 50 storeys reinforced concrete structure and comparison of several provisions. This research study investigates the difference between seismic and wind results between the two codes and if there might be any differences in the structural elements reinforcement amount, which will affect the cost of the building.